REVEALING MOTIVES AND LANGUAGE BEHAVIOR IN A SUICIDE NOTE - Mahfudurido Ilzam (Institut Agama Islam Negeri Palopo, 2019)
Suicide note, one of noteworthy evidences in forensic linguistics, may inform the suicidal behavior of the notewriter, such as the emotional aspects, messages, expectations, motives, and its genuinity. In this article, words, phrases, and sentences employed in a suicide note left by a married young lady were analyzed using lexical semantics, pragmatic semantics, and relevance theory to uncover messages and underlying motives. The procedures began with tabulating and categorizing the words based on their part of speech to see their prominent linguistic features and conducting twofold analysis, namely lexical semantic analysis to find notewriter’s messages and pragmatic semantic analysis and relevance theory to find the underlying motive. The results of lexical semantic analysis showed that the notewriter left a couple of messages like apologies and requests but in an assertive mode to be carried out by the abandoned parties, while the results of pragmatic semantics analysis and relevance theory showed that the motive of the suicide was feeling of failure in carrying out her role as a housewife. Patriarchal culture that puts women in charge of serving the family is also presumably to take part in encouraging the suicide.